What happened to you? : conversations on trauma, resilience, and healing - Perry, Bruce Duncan, 1955-; Winfrey, Oprah (Flatiron Books, 2021)
Oprah Winfrey, sharing stories from her own past, and a renowned brain development and trauma expert discuss the impact of trauma and adversity and how healing must begin with a shift to asking, "What happened to you?" rather than "What's wrong with you?"